Tożsamość człowieka w kontekście relacji natura - kultura - sacrum - Zbigniew Mirek (Jesuit University Ignatianum in Krakow, 2017)
The aim of the article is to draw attention to man's identity in the perspective of relations between nature, culture and sacrum, with special emphasis on the question: "Who is man?" as depicted in the Holy Scriptures. Created by God, man is bestowed the "natural" pursuit of Him and the desire for a full communion with Him. He was named "capax Dei", i.e. "open to God". This openness enables man to discover God, especially in the beauty of the world created by Him. The author notices that, through creative participation in life and building genuine culture and environment, man can fully express his identity. Man's identity is also expressed by the listening to the Word of God. The ability to recognise this Word as well as the truth it includes makes man free and rational. The author believes that nature, as the Word of God, through its beauty, makes that man's identity is also dependant on his communion with nature. Themost perfect illustration of human identity, with man as a listener of the Word of God, is the attitude of Mary expressed in Her words as a reply to God's words manifested to her by Archangel Gabriel. Another significant element in the shaping of man's identity seems the call for discovering God's will and, by its power, mastery over nature and culture. This mastery constitutes an inherent element of man's life and identity. It is important, however, to be able to arm oneself and fight as a Lord's warrior in this combat.